Estimating the Weight Percentage of Acetic Acid in Samples of Commercial Vinegar from Local Markets in Tripoli - Khayriya Rahouma (AlQalam Journal of Medical and Applied Sciences, 2025)
This study aimed to estimate the weight percentage of acetic acid in different samples of commercial vinegar available for consumers in local markets in Tripoli. Indeed, such an estimation would help to determine the quality of the vinegar and ascertain its safety for consumption. Thirteen samples of vinegar were collected: eleven of them were industrial vinegar and two were natural vinegar (i.e., corn vinegar and cane vinegar) from local markets in Tripoli. The volumetric analysis method (neutral titrations) was used to estimate the standard concentration of the samples. This method involves titrating a diluted solution of each vinegar sample using a standard solution of sodium hydroxide with a concentration of 0.0894 N, the concentration of which was previously controlled and known by titrating it with an initial standard solution of potassium hydrogen phthalate. Density was also estimated, and the percentage of acetic acid in all vinegar samples was calculated. The results showed that the percentages of acetic acid in the analyzed samples were between 1.14 wt.% and 5.74 wt.%. In a more accurate sense, the results showed that the percentages of acetic acid in the synthetic vinegar samples were (1.14, 4.72, 4.54, 5.62, 5.02, 2.96, 4.75, 3.82, 5.74, 5.02, 5.12 %wt), respectively. In contrast, the results in the natural vinegar samples were (5.14, 2.56 wt%) for cane vinegar and corn vinegar, respectively. Based on these figures, the researcher would confirm that six of the samples (S4, S5, S9, S10, S11, S12) are within the requirements recommended in the Libyan Standards. Conversely, it was found that nine samples are considered within the Standards recommended by the Food and Agriculture Organization and the World Health Organization. تهدف هذه الدراسة إلى تقدير النسبة المئوية الوزنية لحمض الخليك في عينات مختلفة من الخل التجاري المعروضة للبيع في الأسواق المحلية بمدينة طرابلس لمعرفة مدى جودة الخل، وضمان سلامته للاستهلاك. تم تجميع ثلاثة عشرة عينة من الخل وهي إحدى عشرة عينة من الخل الصناعي وعينتان من الخل الطبيعي (خل الذرة ، وخل القصب) من الأسواق المحلية بمدينة طرابلس، واستخدمت طريقة التحليل الحجمي (معايرات التعادل) لتقدير التركيز المعياري للعينات، وذلك بمعايرة محلول مخفف من كل عينة من عينات الخل باستخدام محلول قياسي من هيدروكسيد الصوديوم تركيزه 0.0894 N والذي تم ضبط ومعرفة تركيزه مسبقاً بمعايرته بمحلول قياسي أولي من فثالات البوتاسيوم الهيدروجينية، كما تم تقدير الكثافة، وحساب النسبة المئوية لحمض الخليك في كل عينات الخل. اظهرت النتائج أن النسبة المئوية لحمض الخليك في العينات التي تم تحليلها كانت في المدى من (1.14) %wt إلى(5.74) %wt, وبمقارنة نتائج تحليل العينات ببعضها أظهرت النتائج أن النسبة المئوية لحمض الخليك في عينات الخل الصناعي التي تم تحليلها كانت (1.14, 4.72, 4.54, 5.62, 5.02, 2.96, 4.75, 3.82, 5.74, 5.02, 5.12) %wt على التوالي, أما بالنسبة لعينات الخل الطبيعي كانت (5.14, 2.56) % wt لخل القصب وخل الذرة على التوالي. أعلى نسبة كانت 5.74) %wt) في العينة (S9), وأقل نسبة كانت (1.14) wt% في العينة (1S). ومن خلال مقارنة النتائج المتحصل عليها بالمواصفة القياسية الليبية. أظهرت النتائج أن ستة من العينات وهي (S4, S5, S9, S10, S11, S12)كانت ضمن الاشتراطات الموصي بها في المواصفة القياسية الليبية، وثلاثة من العينات وهي (S2, S3, S7) كانت أقل بقليل مما هو موصي به في المواصفة، أما العينات الأربعة وهي (S1, S6, S8, S13) كانت اقل بكثير من الاشتراطات الموصي بها في المواصفات القياسية الليبية. وبالمقارنة بمواصفات منظمة الأغذية والزراعة ومنظمة الصحة العالمية (FAO/WHO, 1998). فإن تسعة عينات فقط من أصل ثلاثة عشرة عينة تعتبر ضمن الاشتراطات القياسية